2022
DOI: 10.3390/ma15062104
|View full text |Cite
|
Sign up to set email alerts
|

The Cytocompatibility of Silver Diamine Fluoride on Mesenchymal Stromal Cells from Human Exfoliated Deciduous Teeth: An In Vitro Study

Abstract: Silver diamine fluoride (SDF) has been used for many years for the treatment of caries, and minimally invasive dentistry concepts have made it popular again. The fact that its application does not require the administration of anesthesia makes its use in children more desirable. The aim of this study was to determine the cytotoxicity of two new commercial SDF products: Riva Star (SDI Dental Limited) and e-SDF (Kids-e-Dental) on mesenchymal stromal cells from human exfoliated deciduous teeth (SHEDs). SHEDs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The cytocompatibility results therefore infer that the clinician should use their clinical judgment to prevent direct pulp contact if the healthy or carious dentine covering the pulp has a thickness of less than 1.5 mm. Riva Star, representing an SDF product in this pilot study, showed better cytocompatibility than other assessed SDF products from the literature ( 25 ). Therefore, Riva Star Aqua, from a cytocompatibility point of view, is a suitable clinical choice in addition to the other advantage it possesses over Riva Star of not containing ammonium iodide.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The cytocompatibility results therefore infer that the clinician should use their clinical judgment to prevent direct pulp contact if the healthy or carious dentine covering the pulp has a thickness of less than 1.5 mm. Riva Star, representing an SDF product in this pilot study, showed better cytocompatibility than other assessed SDF products from the literature ( 25 ). Therefore, Riva Star Aqua, from a cytocompatibility point of view, is a suitable clinical choice in addition to the other advantage it possesses over Riva Star of not containing ammonium iodide.…”
Section: Discussionmentioning
confidence: 72%
“…It is important to keep in mind that a dentine bridge of 1.5 mm is considered sufficient to limit the negative effects from eluates from dental materials, and with the carious structure above the pulp that will be remineralized with the SDF products, the possible exposure to the dental pulp also becomes more limited. In addition, the SDF products usually work as a step 1 and step 2 protocol, resulting in a more favorable result for cytocompatibility when combined ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation